Application of the Islamic Market Concept in the Era of the Prophet Zaim Saidi’s Perspective - Yayuli, Yayuli; Hakim, Lukmanul; Isnaini, Anif Nur; Jannah, Nisa’ Zahrotul (Universitas Mercu Buana, 2022)
In the city of Surakarta there is a market that has a different system from the general market. The market is named